Attitude and knowledge towards concussion among doctors and rugby players in Malaysia - Wafa, S.M.Wazien Wafa B. S. Saadun Tarek (2020)
Malaysia is faced with the inadequacy of research studies assessing the attitudes and knowledge towards concussions among doctors and rugby player. This lack of knowledge and unsafe attitudes can lead to short and long term sequelae if a CC is not managed correctly. The poor understanding and misconception regarding concussions could result in a lack of proper reporting and lead to more players and doctors ignoring the injury. This is a cross sectional study among doctors and rugby players in Malaysia to assess knowledge and attitude towards . Self-administered questionnaire, RoCKAS-ST is adopted from previous study. Questionnaire was given to 285 rugby players and 217 doctors with return rate of 63% and 23% respectively. Descriptive analysis and univariate ANOVA was used to analyse the statistical response. Both doctors and rugby players recorded good attitude index compared to other previous study however the knowledge index of rugby players in Malaysia is subpar. There is significant differences in knowledge index among doctors and rugby players in Malaysia More training and education programme regarding should be done in Malaysia to increase the level of knowledge and attitude in both group of rugby players and doctors especially those in emergency medicine, family medicine, sports medicine, neurosurgery, surgery and orthopaedics.